The bioactivities of sclareol: A mini review - Zhou, Jianbo; Xie, Xiaofang; Tang, Hailin; Peng, Cheng; Peng, Fu (Frontiers in Pharmacology, 2022)
Sclareol, a diterpene alcohol isolated from the herbal and flavor plant clary sage (Salvia sclarea L.), is famous and far-famed as the predominant ingredient in the refined oil of Salvia sclarea (L.). The empirical medicine of Salvia sclarea L. focuses on various diseases, such as arthritis, oral inflammation, digestive system diseases, while the sclareol perform more extensive bioactivities, including anti-tumor, anti-inflammation and anti-pathogenic microbes, even anti diabetes and hypertension. However, there is a lack of literatures to integrate and illuminate the bioactivities of sclareol based on well-documented investigations. Interestingly, sclareol was recently reported as the potential candidate against COVID-19 and Parkinson's disease. Thereby, the popular researches concerning on the role of sclareol in cancer, inflammation and further delivery systems are reviewed for comprehensively understanding sclareol’s bioactive attributes and potential application in medicine.